Flashback - Barr, Nevada (New York Berkley, 2004)
Taking a temporary post as ranger in Dry Tortugas National Park to escape dealing with a marriage proposal, Anna Pigeon investigates a mysterious boating accident that leads her to uncover sinister local crimes from the past.
Keywords: Women park rangers -- Florida -- Florida--Fort Jefferson -- Dry Tortugas National Park